Data Science Projects with Python: A Case Study Approach to Successful Data Science Projects Using Python, Pandas, and Scikit-Learn - Klosterman, Stephen (Packt Publishing, Limited, 2019)
Data Science Projects with Python will help you get comfortable with using the Python environment for data science. This book will start you on your journey to mastering topics within machine learning. These skills will help you deliver the kind of state-of-the-art predictive models that are being used to deliver value to businesses across.